(untitled) (Perner’s Contacts, 2022)
The air transport network is one of the most important and critical infrastructures in today’s global economy. Air transport would not be able to operate without the air network. This fact significantly contributed to interest in a closer study of the issue of air network status assessment. The aim of this article is to evaluate the European air network by identifying and evaluating major European airports based on scheduled flights. Robustness of this air network was determined with regard to its evaluation. According to research, a suitable methodology was chosen which is describing the organization of data, specification of the research area and selection of method. Civil international airports which are located in European countries recognized by their entire size and handled at least 1 million passengers in 2018, were chosen as the basis for the creation of the European air network model and following evaluation. For these airports, individual scheduled flights were searched including their frequency during the selected period on 11-17 November 2019. The method of centrality used in the field of graph theory was chosen to evaluate the air network of these selected airports with regard to their connectivity. The obtained results identified the most important airports of the European air network and thus represent status assessment of air network during the winter flight schedule 2019/2020. These results were used to monitor the robustness of the European air network as a whole. The robustness of the air network was monitored based on a simulation of the sequent closure of the most important airports in the network with regard to the change of average path length and the size of the giant component. The European air network becomes inoperable when 19-20% of the best evaluated airports in the network are closed.